2014
DOI: 10.1021/cm5023129
|View full text |Cite
|
Sign up to set email alerts
|

Are Two Azo Groups Better than One? Investigating the Photoresponse of Polymer-Bisazobenzene Complexes

Abstract: Azobenzene chromophores are an ideal choice for material applications where functionality needs to be activated in a precise remote-controlled fashion. The azobenzene stimuli-response falls into two categories, either based on efficient trans-to-cis photoisomerization and a high cis yield enabling on−off type functions, or relying on a fast trans−cis−trans cycling creating motion in the material system. Herein, we show that using bisazochromophores instead of the more common monoazobenzene derivatives makes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 46 publications
(99 reference statements)
1
58
0
Order By: Relevance
“…This is stimulated even more by dual wavelength exposure promoting both excitation of trans and the cis isomer of azobenzene rather than populating cis isomer solely. This dynamics was proposed to be responsible for the lateral transport of azobenzene-modified side-chain polymers under the exposure with an interference pattern of a laser source [49]. Here, we anticipate its importance in our densely cross-linked networks where the dynamics in the azobenzene isomerisation enhances the formation of molecular voids in the polymer matrix resulting in a large volume increase on the macroscopic level.…”
Section: Enhancement Of Volume Increasementioning
confidence: 67%
“…This is stimulated even more by dual wavelength exposure promoting both excitation of trans and the cis isomer of azobenzene rather than populating cis isomer solely. This dynamics was proposed to be responsible for the lateral transport of azobenzene-modified side-chain polymers under the exposure with an interference pattern of a laser source [49]. Here, we anticipate its importance in our densely cross-linked networks where the dynamics in the azobenzene isomerisation enhances the formation of molecular voids in the polymer matrix resulting in a large volume increase on the macroscopic level.…”
Section: Enhancement Of Volume Increasementioning
confidence: 67%
“…The actuation is associated with the light-induced heat generation rather than via trans-cis isomerization since: (i) The excitation wavelength (532 nm) matches neither the trans-cis absorption of azo molecules in the ultraviolet, nor the wavelength for bidirectional isomerization (trans-cis and cis-trans at the same time) in azo molecules around 490 nm [20] ; (ii) The azo molecular concentration (1 wt%) is too low to trigger fast mechanical actuation by photochemical effects; (iii) Strong laser excitation intensity (tens of Watts per cm 2 ) and dye bleaching suggest light-induced heat effects in the system. There are several parameters that govern the stepping dynamics.…”
Section: Communicationmentioning
confidence: 99%
“…This allowed assessing the effect of chromophore polarity, bulkiness, and length on photo-orientation. 91,94,[112][113][114][115] Focusing first on molecules 1-4 (1 = NHA above), which differ only in their substitution at the tail (nonbonding) end of the azobenzene, it was shown that this change was enough to make a drastic difference in the photoresponsive behavior of the complexes. Fig.…”
Section: 107mentioning
confidence: 99%
“…Even though isotropic, photo-orientation was observed in all of these materials, and when comparing P4VP(5) to P4VP (8), it was shown that the larger aspect ratio of 5 gave rise to a 4-fold increase in birefringence when using the same azobenzene concentration. 115 Also, two conclusions of practical importance for the selection of inscription wavelength were drawn. First, the electronic structure of 6 greatly broadened the absorption spectrum, making it possible to inscribe birefringence over a wide range of wavelengths, from 375 nm to 633 nm.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation